Analisa dan Perancangan Sistem Informasi Pusat Data Menggunakan Metode User Centered Design - Nevaldi Amnarisky; Eki Saputra; Syaifullah (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The Information Systems Study Program at Sultan Syarif Kasim State Islamic University as a higher education institution has used information systems that play an important role in operations to support productivity and increase efficiency. The Information Systems Study Program currently has two systems to support operational activities, such as the IRAISE system and the SITASI system. However, these two systems have not been able to provide important data such as achievement data, organizational data, research, publications, seminars & workshops, dedication and intellectual property rights data carried out by lecturers and students. Even though the data is useful in the operational activities of the Information Systems Study Program. The problem that happens is the absence of well-organized information. This is because there is no computer program that acts as a data center that can manage, accommodate and organize this important data, so that if there is no data center system, data collection will take a long time and data recording will be repeated. For this reason, it is necessary to carry out analysis and design before building a data center information system. The data center system must be able to meet the needs and be easily understood by users, therefore a User Centered Design (UCD) method is needed which is an approach in development that focuses on end users. The purposes of using the UCD method  to help determine the relevance of the system interface display based on user needs.